Legal Protection Efforts Against Victims of Embezzlement of Car Rental Vehicles in Review of Article 372 Criminal Code - Rasyadan Fladidzil Ikra (UM Purwokerto Press, 2023)
The difficulty in the community to own a private vehicle does not always have a negative impact on society. The high need for transportation facilities coupled with the low ability of the community to buy private vehicles has resulted in the rental business / rental of private vehicles experiencing a significant increase in business lately. One of the rentals that is much needed for the surrounding community is car rental which is a business in the field of transportation services. The service provided is to rent a car for consumers who need a car for the purposes of departure to a place or out of the area such as family visits, recreation, homecoming, and other consumer needs. In addition to car rental services, it also serves transport / taxi services for consumers. However, on the other hand, there are many cases that befall business actors, including many irresponsible consumers or rentals such as not paying rent for unclear reasons, accidents, and theft to embezzlement. The problems that arise are what are the inhibiting factors in law enforcement of criminal acts of embezzlement of car rental vehicles and how law enforcement against embezzlement of car rental vehicles.